Language, Literature, and Cultural Codes in the Puya Ke Puya Novel by Faisal Oddang: A Study of Semiotics - Damayanti, Ika; Ramly, Ramly; Idawati, Idawati (Journal of Asian Multicultural Research for Social Sciences Study, 2022)
This study aims to examine the form of language code, literary code, cultural code in the novel Puya Ke Puya by Faisal Oddang as teaching materials for prose fiction literature study programs in universities. The research method used is descriptive qualitative research. Data collection techniques are documentation with reading and listening techniques, and recording techniques. Data analysis was carried out through several stages, namely data identification, data classification, description, and drawing conclusions. The results showed that the language codes used in the Puya Ke Puya novel were the use of regional languages in the form of greetings, kinship elements, everyday vocabulary and the use of foreign languages, literary codes depicted in words with connotations and figurative meanings, cultural codes in the novels concerned the system. The culture that exists among the Toraja people such as social organization systems, living equipment systems and technology, and religious systems.